Nucleophilic 18F‐Labeling of Spirocyclic Iodonium Ylide or Boronic Pinacol Ester Precursors: Advantages and Disadvantages. Issue 3 (19th December 2016) - Petersen, Ida Nymann; Kristensen, Jesper Langgaard; Herth, Matthias Manfred
Abstract : The field of labeling electron‐rich aryl compounds with nucleophilic [ 18 F]fluoride has recently expanded with radiofluorination strategies that apply boronic esters or spirocyclic iodonium ylides as precursors. Herein, we present a direct comparison of these strategies by using nine chemically diverse model compounds. In general, spirocyclic iodonium ylides outperform the boronic esters. Abstract : The field of labeling electron‐rich aryl compounds with nucleophilic [ 18 F]fluoride has recently expanded. Promising and improved radiofluorination strategies use boronic esters or spirocyclic iodonium ylides as precursor moieties. Herein, we directly compare these strategies by using nine chemically diverse model compounds. In general, spirocyclic iodonium ylides are the preferred precursors.